DIVERSIFIKASI PRODUK OLAHAN DARI UBI JALAR - Indah, Dwi (SOLIDEO Jurnal Pengabdian Masyarakat, 2025)
Sweet potato (Ipomoea batatas L) is also known as sweet potato is a secondary crop, which contains high carbohydrates, so it can function as a substitute for staple foods (besides rice). The purpose of the activity in the Community is to provide knowledge through training to housewives to increase income by increasing the added value of sweet potatoes and empowering housewives. This activity can improve the skills of mothers and can also produce healthy and nutritious products. In addition, this activity is an effort to socialize the improvement of nutrition and food security in the community.